Consumer preferences for emerging trends in organics: product origin and scale of supply chain operations - Pozo, Veronica F. (Kansas State University, 2009)
Notable changes are occurring in the U.S. organic food sector. First, the U.S. organic food system is increasingly relying on imports, because the expansion in the organic production has failed to satisfactorily meet the rapidly growing demand for organic foods. Second, the “locally grown” concept has become appealing to consumers, with some evidence of consumers switching from certified organic foods to local, conventional foods. Third, organic food has penetrated the mass-market channel, and organic foods are no longer being sold exclusively in natural product stores. And fourth, the social and environmental awareness among consumers is increasing. Thus, consumers are also willing to pay a price premium to support small farmers. To understand how these changes are affecting the demand for organic foods, this study used survey data to assess U.S. consumers‟ preferences for fresh organic apples that are sourced from various places and from supply chain operations that vary in scale. The survey was administered via the Internet to a random sample of 285 households across the U.S through a research company. Choice experiment was selected as the valuation method. Results indicate that among the levels of the location attributes, the “locally grown” label was associated with the highest average WTP. The “regionally grown” was the second most preferred, “U.S. grown” the third, and “imported” the least. The “locally grown” label was valued higher than the “certified organic label”. Also, consumers were willing to pay a higher value for apples produced on a small farm compared to those from a large farm. However, they did not distinguish the type of retail outlets where apples were offered. The analysis incorporating the effects of consumer characteristics suggest that the perceived importance of public benefits impacted the values of origin attributes more than the private ones; the type of retail outlet attributes became significant among certain gender and age segments; and the value of small farm attribute increased with consumers‟ income. Finally, results from a theoretical model suggest that the variability in the WTP obtained among the origin attributes could be explained by the reputation of product quality depending on their origin.
Keywords: Organic food; Origin; Type of retail outlet; Size of farm; Collective reputation; Choice experiment; Economics, Agricultural (0503)